DIAGNOSIS AND MANAGEMENT BENIGN PAROXYSMAL POSITIONAL VERTIGO (BPPV) - Purnamasari, Putu Prida (E-Jurnal Medika Udayana; vol 2 no6(2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Benign Paroxysmal Positional Vertigo (BPPV) is one of the most frequent Neurotology disorders. Benign Paroxysmal Positional Vertigo is a vestibular disorder in which 17% -20% of patients complained of vertigo. In the general population the prevalence of BPPV is between 11 to 64 per 100,000 (prevalence 2.4%). Benign Paroxysmal Positional Vertigo is a disturbance in the inner ear with positional vertigo symptoms that occur repeatedly with the typical nystagmus paroxysmal. The disorders can be caused either by canalithiasis or cupulolithiasis and could in theory be about three semicircular canals, although superior canal (anterior) is very rare. The most common is the form of the posterior canal, followed by a lateral. The diagnosis of BPPV can be enforced based on history and physical examination, including some tests such as Dix-Hallpike test, caloric test, and Supine Roll test. The diagnosis of BPPV is also classified according to the types of channels. Management of BPPV include non-pharmacological, pharmacological and operations. Treatment is often used non-pharmacological includes several maneuvers such as Epley maneuver, Semount maneuver, Lempert maneuver, forced prolonged position and Brandt-Daroff exercises. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: BPPV, Nystagmus, Maneuver.